Ultrasound-Promoted Synthesis of 4-Pyrimidinols and Their Tosyl Derivatives - Caroli-Rezende, M; Dominguez-Caru, M; Vidal-Palomo, M; Vidal-Palomo, M (Georg Thieme Verlag, 2016)
Ultrasound irradiation promoted the cyclocondensation of β-keto esters and amidines in good to excellent yields to form sixteen highly substituted 4-pyrimidinols. Tosylation of these compounds, in another ultrasound-promoted conversion, formed 4-pyrimidyl tosylates in high yields. The use of the developed protocol as an alternative route to 4-arylpyrimidines was illustrated with three examples of the Suzuki-Miyaura cross-coupling of the prepared tosylates with phenylboronic acid. © Georg Thieme Verlag Stuttgart New York-Synthesis.